The image of the father in the poetry of Sharif Al-Radhi - kareem, Delal Hashim; Yascen, Mohamed Taha (Al-Adab Journal, 2015)
The technical study for analyzing the litrary texts requires externaleffects that contribute in descriptive creativity , like social fastors and psychological impulses . And with the reality of these impulses the picture of (father), Al- shareef Al Radhi had described , this picture can be clarified . Using embodiment and personification Focusing on the supreme ancestry to our prophet to show the picture ihits best condition, using embodiment and personification to transfer morality to sensibility so as to promote the fathers level , employing some of the syntax manncrs to verify the imaginary picture of the father.Based on logic , imagintimn had changed to reality with the technical creativily to stabilize the very close description , mentioning the most important features that Arabs have like courage and excitement Every thing that poet had atteptef was to stabilize and honor personality and to evaluate the principle of inherite of an expected dominancy that the poet had ambihion about